Supporting Collaborative Ideation Through Freehand Sketching of 3D-Shapes in 2D Using Colour - Sandnes, Frode Eika; Lianguzov, Yuriy; Rodrigues, Osmar Vicente [UNESP]; Lieng, Henrik; Medola, Fausto Orsi [UNESP]; Pavel, Nenad (Springer Nature, 2017)
The modelling of 3D shapes is a challenging problem. Many innovative approaches have been proposed, however most 3D software require advanced skills that hinders collaboration and spontaneous ideation. This paper proposes a novel framework that allows designers to express their ideas in 3D space without extensive training such that they can reuse their 2D sketching skills collaboratively in teams.
Keywords: 3D-modelling; Collaborative design; Color-map; Sketching